Accelerated humification and alteration of microbial communities by distillers' grains addition during rice straw composting. (December 2021) - Ren, Liheng; Yan, Binghua; Kumar Awasthi, Mukesh; Zhang, Jiachao; Huang, Hongli; Zhang, Lihua; Luo, Lin
Graphical abstract: Highlights: Humification was accelerated by distillers' grains addition during composting. OM degradation and nitrogen conservation were promoted by addition. Nutritional status and microbial communities were significantly changed by addition. Nitrate, WSC, OM, ammonium were the key factors influencing bacterial community. WSC significantly affected the dominant fungal community dynamics. Abstract: This research explored the influence of distillers' grains amendment on the humification performance and microbial communities during rice straw composting. The composition of dissolved organic matter and maturity index were analyzed by the fluorescence excitation emission matrix spectroscopy and parallel factor analysis. High-throughput sequencing and redundancy analysis were employed for revealing the structure dynamics for microbial community and their shaping factors, respectively. Results indicated that addition of distillers' grains effectively increased the microbial activity, which was beneficial to the organic matter degradation and nitrogen conservation. Microbial community structures were significantly changed with different amendment strategies. Nitrate, water soluble carbon, organic matter, ammonium were the key parameters influencing the variation of bacterial community in different treatments. Water soluble carbon significantly affected the dominant fungal community dynamics. These results showed that addition of distillers' grains effectively improved the nutritional status and changed the microbial communities during rice straw composting.